Chemotherapy Options beyond the First Line in HER-Negative Metastatic Breast Cancer. (29th November 2020) - Lorusso, Vito; Latorre, Agnese; Giotta, Francesco
Abstract : Despite the recent advances in the biological understanding of breast cancer (BC), chemotherapy still represents a key component in the armamentarium for this disease. Different agents are available as mono-chemotherapy options in patients with locally advanced or metastatic BC (MBC) who progress after a first- and second-line treatment with anthracyclines and taxanes. However, no clear indication exists on what the best option is in some populations, such as heavily pretreated, elderly patients, triple-negative BC (TNBC), and those who do not respond to the first-line therapy. In this article, we summarize available literature evidence on different chemotherapy agents used beyond the first-line, in locally advanced or MBC patients, including rechallenge with anthracyclines and taxanes, antimetabolite and antimicrotubule agents, such as vinorelbine, capecitabine, eribulin, ixabepilone, and the newest developed agents, such as vinflunine, irinotecan, and etirinotecan.